Draft genome sequence of a marine actinobacteria Sciscionella strain SE31 - Teo, W.F.A.; Wee, W.Y.; Choo, S.W.; Tan, G.Y.A. (Elsevier, 2015)
The bacterium strain SE31, a member of the genus Sciscionella, was isolated from intertidal sediments collected from Cape Rachado, Malaysia. The high quality draft genome sequence of Sciscionella strain SE31 with a genome size of approximately 7.4. Mbp is reported. Preliminary analysis revealed 46 putative gene clusters involved in the biosynthesis of secondary metabolites and 113 putative genes that are associated with bacterial virulence, disease and defense. Availability of the genome sequence of Sciscionella SE31 will contribute to a better understanding of the genus Sciscionella.